A novel circular RNA, circIgfbp2, links neural plasticity and anxiety through targeting mitochondrial dysfunction and oxidative stress-induced synapse dysfunction after traumatic brain injury - Du, Mengran; Wu, Chenrui; Yu, Renqiang; Cheng, Yuqi; Tang, Zhaohua; Wu, Biying; Fu, Jiayuanyuan; Tan, Weilin; Zhou, Qiang; Zhu, Ziyu; Balawi, Ehab; Huang, Xuekang; et al. (Molecular psychiatry, 2022)
Traumatic brain injury (TBI) can lead to different neurological and psychiatric disorders. Circular RNAs (circRNAs) are highly expressed in the nervous system and enriched in synapses; yet, the underlying role and mechanisms of circRNAs in neurological impairment and dysfunction are still not fully understood. In this study, we investigated the expression of circRNAs and their relation with neurological dysfunction after TBI. RNA-Seq was used to detect differentially expressed circRNAs in injured brain tissue, revealing that circIgfbp2 was significantly increased. Up-regulated hsa_circ_0058195, which was highly homologous to circIgfbp2, was further confirmed in the cerebral cortex specimens and serum samples of patients after TBI. Moreover, correlation analysis showed a positive correlation between hsa_circ_0058195 levels and the Self-Rating Anxiety Scale scores in these subjects. Furthermore, knockdown of circIgfbp2 in mice relieved anxiety-like behaviors and sleep disturbances induced by TBI. Knockdown of circIgfbp2 in H 2 O 2 treated HT22 cells alleviated mitochondrial dysfunction, while its overexpression reversed the process. Mechanistically, we discovered that circIgfbp2 targets miR-370-3p to regulate BACH1, and down-regulating BACH1 alleviated mitochondrial dysfunction and oxidative stress-induced synapse dysfunction. In conclusion, inhibition of circIgfbp2 alleviated mitochondrial dysfunction and oxidative stress-induced synapse dysfunction after TBI through the miR-370-3p/BACH1/HO-1 axis. Thus, circIgfbp2 might be a novel therapeutic target for anxiety and sleep disorders after TBI.